2015
DOI: 10.2169/internalmedicine.54.3597
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Progressive Interstitial Lung Disease Associated with Dermatomyositis Treated with Combination of Immunosuppressive Therapy, Direct Hemoperfusion with a Polymyxin B Immobilized Fiber Column and Intravenous Immunoglobulin

Abstract: Rapidly progressive interstitial lung disease (ILD) is associated with dermatomyositis (DM) and has a high mortality rate even with immunosuppressive agents. For such cases, there is no evidence on the combined effect of direct hemoperfusion with a Polymyxin B immobilized fiber column and intravenous immunoglobulin. We herein report a case of 61-year-old woman who presented with respiratory failure. She showed ILD associated with DM which did not improve with immunosuppressive agents, but was improved with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Several case reports similarly documented improvement in patients treated for rapid progressive interstitial pneumonia with dermatomyositis. 10,11,29,30 In the 12 patients with dermatomyositis in our study (5 with and 7 without PMX-DHP), the survival proportion was better when PMX-DHP treatment was administered. Teruya et al reported a successful response to PMX-DHP in a patient with amyopathic dermatomyositis who developed RP-ILD characterized by elevated anti-MDA5 autoantibodies.…”
Section: Discussionmentioning
confidence: 58%
“…Several case reports similarly documented improvement in patients treated for rapid progressive interstitial pneumonia with dermatomyositis. 10,11,29,30 In the 12 patients with dermatomyositis in our study (5 with and 7 without PMX-DHP), the survival proportion was better when PMX-DHP treatment was administered. Teruya et al reported a successful response to PMX-DHP in a patient with amyopathic dermatomyositis who developed RP-ILD characterized by elevated anti-MDA5 autoantibodies.…”
Section: Discussionmentioning
confidence: 58%
“…[ 11 ] Case reports Anti-Jo-1 AS-ILD 3 1–5x30–40 g up to 9 courses CS, CYC Improvement of dyspnea and chest CT (in 2 patients) Takai et al. [ 12 ] Case report Anti-Jo-1 AS-ILD 1 20 g for 5 days CS, MPT, CYC, CYa, Polymyxin B Recovered acute phase, improvement of dyspnea and interstitial changes Suzuki et al. [ 14 ] Case report Anti-Jo-1 AS-ILD.…”
Section: Discussionmentioning
confidence: 99%
“…IVIG increased FVC, DLCO and decreased the mean prednisolone dose over time. Three other AS-ILD case reports [ [10] , [11] , [12] ] describe clinical improvement after treatment with IVIG. However, Hervier et al.…”
Section: Discussionmentioning
confidence: 99%
“…Teruya et al 11 demonstrated serial reductions in circulating immune complexes after the use of PMX-DHP, suggesting that this treatment may work to directly remove anti-MDA5 complexes as well. Based on these hypotheses, PMX-DHP has been used for treatment of adult patients with anti-MDA5 dermatomyositis-associated RP-ILD 8,11,13 …”
Section: Discussionmentioning
confidence: 99%
“…As the patient continued to worsen on traditional aggressive therapy, at the family's request, a literature review was conducted to investigate possible novel treatments in patients with RP-ILD. PMX-DHP was considered based on recent evidence, suggesting improved outcomes for adult patients with acute respiratory distress syndrome 10 and RP-ILD 11,13 . After discussion with the ChILD program, as well as with the manufacturer (Toray Medical Inc, Tokyo, Japan.…”
Section: Case Reportmentioning
confidence: 99%